Does the long-term success of REDD+ also depend on biodiversity?. Issue 2 (10th October 2014) - Hinsley, Amy; Entwistle, Abigail; Pio, Dorothea V.
Abstract: Originally proposed in 2005 as a way to use financial incentives to tackle global climate change, Reducing Emissions from Deforestation and forest Degradation (REDD) has evolved to include conservation, sustainable management of forests and enhancement of forest carbon stocks, in what is now known as REDD+. Biodiversity protection is still viewed principally as a co-benefit of the REDD+ process, with conservation of forest tree cover and carbon stocks providing the main measure of success. However, focusing solely on tree cover and carbon stocks does not always protect other species, which may be threatened by other factors, most notably hunting. We present evidence from the literature that loss of biodiversity can affect forest composition, tree survival and forest resilience and may in some cases ultimately lead to a reduction in carbon storage. We argue that REDD+ projects should specifically mitigate for threats to biodiversity if they are to maximize carbon storage potential in the long term.